2011
DOI: 10.1111/j.1365-294x.2011.05177.x
|View full text |Cite
|
Sign up to set email alerts
|

Heterozygosity and survival in blue tits (Cyanistes caeruleus): contrasting effects of presumably functional and neutral loci

Abstract: The relationship between genetic diversity and fitness has important implications in evolutionary and conservation biology. This relationship has been widely investigated at the individual level in studies of heterozygosity-fitness correlations (HFC). General effects caused by inbreeding and/or local effects at single loci have been used as explanations of HFC, but the debate about the causes of HFC in open, natural populations is still ongoing. Study designs that control for variation in the inbreeding level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
134
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 62 publications
(141 citation statements)
references
References 71 publications
(179 reference statements)
7
134
0
Order By: Relevance
“…Previous studies carried out on this species found significant heterozygosity–fitness correlations considering different life‐history traits (reproductive performance: Foerster, Delhey, Johnsen, Lifjeld, & Kempenaers, 2003; García‐Navas, Ortego, & Sanz, 2009; Olano‐Marin, Mueller, & Kempenaers, 2011b; survival probability: Olano‐Marin, Mueller, & Kempenaers, 2011a; and parasite resistance: Ferrer, García‐Navas, Sanz, & Ortego, 2014). Consanguineous matings have been reported in these populations (Ferrer et al., 2014; García‐Navas et al., 2009), which may increase variance in inbreeding and the chance of detecting HFC due to extensive ID across the genome (Balloux et al., 2004; Szulkin et al., 2010).…”
Section: Introductionmentioning
confidence: 82%
See 4 more Smart Citations
“…Previous studies carried out on this species found significant heterozygosity–fitness correlations considering different life‐history traits (reproductive performance: Foerster, Delhey, Johnsen, Lifjeld, & Kempenaers, 2003; García‐Navas, Ortego, & Sanz, 2009; Olano‐Marin, Mueller, & Kempenaers, 2011b; survival probability: Olano‐Marin, Mueller, & Kempenaers, 2011a; and parasite resistance: Ferrer, García‐Navas, Sanz, & Ortego, 2014). Consanguineous matings have been reported in these populations (Ferrer et al., 2014; García‐Navas et al., 2009), which may increase variance in inbreeding and the chance of detecting HFC due to extensive ID across the genome (Balloux et al., 2004; Szulkin et al., 2010).…”
Section: Introductionmentioning
confidence: 82%
“…Individuals recaptured the following breeding season in any nestbox plot from the study area (see Figure 1 in Ferrer et al., 2016) were coded as “1”, whereas those that were not recovered in the next year were coded as “0” (e.g., Olano‐Marin, Mueller, & Kempenaers, 2011a). Our capture effort (i.e., the proportion of individuals captured among all those breeding in our study populations) was high (82.72%), and as a result, the proportion of birds classified as “nonrecruited” but returning as breeders in subsequent years (i.e., individuals that actually survived but were not captured in year t  +   1) was low (13.1%).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations